On Covering Radius of Orthogonal Arrays - Boumova, Silvia; Ramaj, Tedis; Stoyanova, Maya (2020 Algebraic and Combinatorial Coding Theory (ACCT), 2020)
We obtain analytically upper bounds for the covering radius of orthogonal arrays (OAs) by investigations of the set of all feasible distance distributions of the corresponding OAs. We apply a procedure for reduction of the possible distance distributions of OA to improve the bound by 1 under certain assumptions. Examples of OAs attaining and close to our bounds are shown.